Phenotypic trends of dairy cattle populations in the regions of the Volga Federal District - N. V. Semenova (Аграрная наука Евро-Северо-Востока, 2018)
The article provides the results of the analysis of historical trends in the development of dairy cattle breeding in 1950-2016 in all kinds of economies: in the Republics of Mordovia, Udmurtia, Chuvashia, Bashkortostan, Mari El, Tatarstan, in Penza, Samara, Saratov, Ulyanovsk, Nizhny Novgorod, Orenburg and Perm regions (the number of cows, an average milk yield and milk production). To smooth random fluctuations of the time series levels the simple moving average method was used. Regression analysis allowed us to obtain the average annual increase/decrease trends for enlarged periods. The results were compared at the regional level. The study revealed that the relative trends for number of cows in all regions of the Volga Federal District ranged from +1.3 to +2.9% up to 1980, and from -4.2 to -1.2% after 1980. Relative growth rates of the average annual milk yield ranged from +0.3 to +5.6%. Since 1950 up to 1990 in regions under study the total milk production was increasing every 10 years. The highest growth rate was observed in Mari El Republic (4.0%), while in the Udmurt Republic, Tatarstan and Samara region it stayed almost at the same level (+3.0%...+3.2%), in other regions it ranged from +1.8 to +2.9%. Since 1990 the annual decline in milk production was noted in Chuvash Republic (-1.2%), Mari El Republic (-2.1%), Penza region (-3.3%) and Ulyanovsk region (-3.9%). In the Republics of Bashkortostan, Udmurtia, Tatarstan and in Saratov region by the end of 2010 the total milk production had increased but in 2015 it declined. At the same time by 2015 in Perm, Nizhny Novgorod and Samara regions the tendencies for milk production had increased.